Analysis of IDO-dependent Immunomodulatory Effect of Mice Fetal Liver Mesenchymal Stem Cells Prior to and After Cryopreservation - Dimitrov, Aleksey Yu.; Dubrava, Tatyana G.; Goltsev, Anatoliy N. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):184.